Effects of cyanobacteria Oscillatoria sp. lipopolysaccharide on B cell activation and Toll-like receptor 4 signaling. (5th June 2017) - Swanson-Mungerson, Michelle; Incrocci, Ryan; Subramaniam, Vijay; Williams, Philip; Hall, Mary L.; Mayer, Alejandro M.S.
Highlights: Oscillatoria sp. LPS activates murine B cells to proliferate and produce IgM. Oscillatoria sp. LPS activates murine B cells to express activation markers and increase phagocytosis. Oscillatoria sp. LPS is not as potent as E. coli LPS regarding B cell activation. Oscillatoria sp. LPS induces altered signaling through Toll like receptor 4 (TLR4). Abstract: Cyanobacteria ("blue-green algae"), such as Oscillatoria sp., are a ubiquitous group of bacteria found in freshwater systems worldwide that are linked to illness and in some cases, death among humans and animals. Exposure to cyanobacteria occurs via ingestion of contaminated water or food-products. Exposure of the gut to these bacteria also exposes their toxins, such as lipopolysaccharide (LPS), to B cells in the gut associated lymphoid tissue. However, the effect of Oscillatoria sp. LPS on B cell activation is unknown. To test the hypothesis that Oscillatoria sp. LPS exposure to murine B cells would result in B cell activation, murine B cells were incubated in the absence or presence of Oscillatoria sp. LPS or E. coli LPS as a positive control. The data indicate that Oscillatoria sp. LPS induces B cells to proliferate, upregulate MHC II and CD86, enhance antigen uptake and induce IgM production at low levels. Additional studies demonstrate that this low level of stimulation may be due to incomplete TLR4 signaling induced by Oscillatoria sp. LPS, since IRF-3 is not induced in B cells after stimulation with Oscillatoria sp. LPS. These findings have important implications for the mechanisms of toxicity of cyanobacteria in both humans and animals.